(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2025)
Abstract: This article presents the unpublished typescript of Mario Talamanca’s paper on homologia kyria, originally delivered at the 1977 Symposion on Greek and Hellenistic Law in Chantilly, France, but never included in the published proceedings. The rediscovered text not only fills a nearly fifty-year gap in the historiography but also provides a valuable contribution to one of the most debated issues in the study of Greek private law in general and of Attic law in particular. Against the background of the influential thesis of H.J. Wolff, which explained the homologia in terms of Zweckverfügung and denied its promissory character, Talamanca advanced a critical reading of the Attic sources, stressing instead the consensual dimension of homologein. His argumentation – grounded in close philological analysis and in a systematic critique of Romanist categories projected onto the Greek experience – shows that the law on homologia kyria cannot be reduced to a mere procedural mechanism, nor does it admit the existence of fully consensual contracts in Athens. Rather, Talamanca outlined a third way: in Attic law the principle of consensuality had not yet taken hold, but the significance of a mere undertaking cannot, in any case, be excluded. The publication of this essay, long forgotten and now restored to the scholarly community, seeks not only to pay tribute to one of the most original interpreters of Greek legal history in the twentieth century, but also to reopen the debate on the nature and limits of contractual obligation in the Athenian polis. Riassunto: L’articolo presenta il dattiloscritto della relazione inedita di Mario Talamanca sull’homologia kyria, originariamente pronunciata al Symposion sul diritto greco ed ellenistico svoltosi a Chantilly, in Francia, nel 1977, ma mai confluita negli atti a stampa. Il testo, oggi riscoperto, non solo colma un vuoto quasi cinquantennale nella storiografia, ma offre anche un contributo prezioso a uno dei temi pi. discussi nello studio del diritto privato greco in generale e attico in particolare. Sullo sfondo della nota tesi di H.J. Wolff, che interpretava l’homologia in base al concetto di Zweckverfügung, negandone il carattere promissorio, Talamanca avanzava una lettura critica delle fonti attiche, ponendone in rilievo la dimensione consensuale. La sua argomentazione – fondata su un’analisi filologica puntuale e su una sistematica critica all’applicazione di 2 categorie romanistiche alla realt. greca – mostra come la disciplina dell’homologia kyria non possa ridursi a un mero meccanismo processuale, né possa tuttavia condurre ad ammettere l’esistenza ad Atene di veri e propri contratti consensuali. Talamanca deline. piuttosto una terza via: nel diritto attico non si era ancora affermato il principio della consensualit., ma la rilevanza del mero impegno non pu. essere in ogni caso esclusa. La pubblicazione di questo saggio, a lungo dimenticato e oggi restituito alla comunit. scientifica, intende non solo rendere omaggio a uno degli interpreti pi. originali della storia giuridica greca nel Novecento, ma anche riaprire il dibattito sulla natura e sui limiti dell’obbligazione contrattuale nella polis ateniese.